Legal culture across the Alps during the post-Carolingian period (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
Scholarship on the eleventh century has stressed the central place that Lombardy had in the early Middle Ages for the revival of legal culture in medieval europe. After having retraced these studies and discussed how this same region had already played an important role for the shaping of legal culture across the Alps during the Ottonian period, my paper focuses on Canon law. Until recent years little or no attention has been paid to the history of Canon law in the decades around 900. According to the classic narrative on this period, it was only in the eleventh century that something new took place in the history of Canon law, specifically the development of canonical collections which aimed not only to systematically re‐arrange, but also to re‐shape a vast number of norms inherited from the previous centuries. Looking at the canonical collection Anselmo dedicata, produced in northern Italy for the Archbishop of Milan, Anselm II (882‐896), this paper aims to highlight the pivotal role played by Lombardy in the shaping of Canon law across the Alps during post‐Carolingian period.
Keywords: Cultura giuridica; collezioni canoniche altomedievali; Anselmo dedicata; Alpi